Addressing global challenges and quality education : 15th European Conference on Technology Enhanced Learning, EC-TEL 2020, Heidelberg, Germany, September 14-18, 2020, Proceedings /: 15th European Conference on Technology Enhanced Learning, EC-TEL 2020, Heidelberg, Germany, September 14-18, 2020, Proceedings. ([2020]) - Unknown
No abstract available